Veldwerk : Kunstenplatform PLAN B : 2020-2021. - Allemeersch, Leontien; Focquet, Vincent; Snauwaert, Kim; Vermote, Ewoud; Kunstenplatform PLAN B (Jette : Infiltro vzw - Ewoud Vermote, 2021)
Ballesteros, Inès ; Dal Brollo, Michela ; Cornelussen, Pim ; Grommen, Ciel ; Royakkers, Maximiliaan ; Pairon, Max ; Sampers, Sibran ; Vancoillie, Maxime ; Vanhellemont, Maite ; Villa, Bert
boek